2022
DOI: 10.1101/2022.10.11.511790
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Single Cell Transcriptomics Reveals the Hidden Microbiomes of Human Tissues

Abstract: The human microbiome has been studied extensively across sites in the body that are readily accessible to sampling. Internal organs and tissues, however, have remained largely unexplored and, in the absence of infectious disease, are widely assumed to be free of microorganisms. Using single-cell transcriptomic data from the Tabula Sapiens spanning 15 human organ donors, 20 tissues, 400,000+ annotated cells, 100+ cell types, and ~70 billion sequences, we created an atlas of the healthy human tissue microbiome w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 131 publications
1
7
0
Order By: Relevance
“…65.99% of reads assigned to Rfam-annotated compactors, Prokaryotes (2.1M reads; 20.64%), Archaea (871K reads; 8.28%), and Microsporidia (432K reads; 4.11%). Some detected rRNA could represent contamination or microbiome composition, as has also been reported by a recent microbial analysis of human single cells (Mahmoudabadi, Tabula Sapiens Consortium, and Quake, n.d.) (Supplement). The most abundant non-ribosomal noncoding RNA was U6-snRNA (28K reads; 0.26%), a small nuclear RNA and one of the core components of the spliceosome (Supplement).…”
Section: Nomad+ Detects Transcript Diversity In Repetitive Rna Loci I...supporting
confidence: 63%
See 1 more Smart Citation
“…65.99% of reads assigned to Rfam-annotated compactors, Prokaryotes (2.1M reads; 20.64%), Archaea (871K reads; 8.28%), and Microsporidia (432K reads; 4.11%). Some detected rRNA could represent contamination or microbiome composition, as has also been reported by a recent microbial analysis of human single cells (Mahmoudabadi, Tabula Sapiens Consortium, and Quake, n.d.) (Supplement). The most abundant non-ribosomal noncoding RNA was U6-snRNA (28K reads; 0.26%), a small nuclear RNA and one of the core components of the spliceosome (Supplement).…”
Section: Nomad+ Detects Transcript Diversity In Repetitive Rna Loci I...supporting
confidence: 63%
“…Table 1). Some detected rRNA could represent contamination or microbiome composition, as has also been reported by a recent microbial analysis of human single cells (Mahmoudabadi, Tabula Sapiens Consortium, and Quake 2023). The most abundant non-ribosomal noncoding RNA was U6-snRNA (RNU6) (22K reads; 0.22% of all Rfam-annotated reads), a small nuclear RNA involved in the spliceosome.…”
Section: Splash+ Detects Transcript Diversity In Repetitive Rna Loci ...mentioning
confidence: 52%
“…Recent studies have shown that the heterogeneity in microbiota and the present cell types along with their functions are co-dependent 25 . Cell-associated microbial reads can be identified in scRNA-seq data 26 .…”
Section: Discussionmentioning
confidence: 99%
“…As detailed in the previous study, we devoted five 10X lanes to deeply sequence ~200 negative control samples derived from reagents and instruments used during the experimental protocols 23 . While these samples were collected post tissue processing experiments, they were acquired from the same batch or from the same exact sample used in the experiments that were then stored in freezers.…”
Section: Models Built On Genus-or Species-level Taxa Provide the Best...mentioning
confidence: 99%
“…Study design. The Tabula Sapiens Microbiome (TSM) dataset derived from searching through human tissue derived droplets (empty or containing cells) as previously described by Mahmoudabadi et al 23 In this study various feature tables (shown in blue) are constructed where the droplets are rows and taxa are columns. The table holds the relative abundance of each taxa in each droplet.…”
Section: Introductionmentioning
confidence: 99%